THE PROBLEMS OF PREPARATION COMPETENT TECHNICAL SPECIALIST IN THE PEPUBLIC OF KAZAKHSTAN - Ginayatovich, Zhanbirov Zhumazhan; Myrzahanovna, Kantarbayeva Shyryn; Zhambylovna, Tursymbekova Zakira; Sovethanovna, Smagulova Aigerim (European Scientific Journal, ESJ, 2014)
The basic task of education is training of specialists who are capable for effective participation in the industrial-innovative development of the country. In connection with it qualitatively new approaches of training and the creation of effective education system directly effect on development of a technical science innovative processes in republic and integration of domestic scientific researchers at world level. President of the Republic of Kazakhstan Nursultan Nazarbayev emphasized that "With the growth of economic indicators increased attention should be paid to improvement of cultural and educational level of our society, the formation of a new intellectual Kazakh nation. To assess the existing problems of improving the quality of training of competent technical staff in the universities of Kazakhstan have been used such methods as empirical research, analysis of engineering and production problems in these sphere. The solution of tasks aimed at improvement of the training of the modern national and competent engineers in the technical colleges, whose implementation is possible, only through a deep theoretical understanding of the national mentality. Conclusion. The system of technical higher education should not only provide one of the main components of the innovation economy - human, but also fulfill the role of a bridge linking education, science and production in all sectors and regions of the country. Therefore the main task of meaningful training of engineers is to describe the processes of studying of new knowledge and changes in thinking, which is the ability to make independent judgments and enables as to form our own point of view.The basic task of education is training of specialists who are capable for effective participation in the industrial-innovative development of the country. In connection with it qualitatively new approaches of training and the creation of effective education system directly effect on development of a technical science innovative processes in republic and integration of domestic scientific researchers at world level. President of the Republic of Kazakhstan Nursultan Nazarbayev emphasized that "With the growth of economic indicators increased attention should be paid to improvement of cultural and educational level of our society, the formation of a new intellectual Kazakh nation. To assess the existing problems of improving the quality of training of competent technical staff in the universities of Kazakhstan have been used such methods as empirical research, analysis of engineering and production problems in these sphere. The solution of tasks aimed at improvement of the training of the modern national and competent engineers in the technical colleges, whose implementation is possible, only through a deep theoretical understanding of the national mentality. Conclusion. The system of technical higher education should not only provide one of the main components of the innovation economy - human, but also fulfill the role of a bridge linking education, science and production in all sectors and regions of the country. Therefore the main task of meaningful training of engineers is to describe the processes of studying of new knowledge and changes in thinking, which is the ability to make independent judgments and enables as to form our own point of view.